VCP and PSMF1: Antagonistic regulators of proteasome activity - Clemen, Christoph S.; Marko, Marija; Strucksberg, Karl-Heinz; Behrens, Juliane; Wittig, Ilka; Gaertner, Linda; Winter, Lilli; Chevessier, Frederic; Matthias, Jan; Türk, Matthias; Tangavelou, Karthikeyan; Schütz, Johanna; et al. (Biochemical and Biophysical Research Communications, 2015)
Protein turnover and quality control by the proteasome is of paramount importance for cell homeostasis. Dysfunction of the proteasome is associated with aging processes and human diseases such as neurodegeneration, cardiomyopathy, and cancer. The regulation, i.e. activation and inhibition of this fundamentally important protein degradation system, is still widely unexplored. We demonstrate here that the evolutionarily highly conserved type II triple-A ATPase VCP and the proteasome inhibitor PSMF1/PI31 interact directly, and antagonistically regulate proteasomal activity. Our data provide novel insights into the regulation of proteasomal activity.
EVALuna2:7290